D day landings : The story of the Allied invasion - Platt, Richard (London : DK Pub, 2004)
Describes the background, events, and consequences of the Allied landing in Normandy, France on June 6, 1944.
Includes index.
Keywords: World War -- 1939-1945 -- Campaigns -- France -- Normandy